Decrease of Thrombosis in Microsurgical Anastomoses: The Use of Intraoperative Pure Intraluminal Unfractionated Heparin - Ramelli, Eloi; Durry, Anastasia; Ruffenach, Laetitia; Bruant-Rodier, Catherine; Bodin, Fredéric (Journal of Reconstructive Microsurgery, 2020)
Background Unfractionated heparin has anticoagulant properties by catalyzing antithrombin III, which inactivates coagulation enzymes. Used in microsurgery, it would prevent the occurrence of thrombosis during microsurgical anastomoses. The objective of this study was to evaluate the role of intraoperative irrigation of the vascular lumen with pure sodium heparin to prevent vascular thrombosis after end-to-end microsurgical anastomoses.Methods End-to-end anastomoses were performed on rats by 21 operators. Three surgical sites were studied (cervical, femoral, and rat tail). The first vessel was irrigated with physiological salt solution (0.9%) before, during, and before the end of the anastomosis. Whenever possible, the contralateral vessel was irrigated with pure unfractionated heparin 5,000 UI/mL. The primary endpoint was the occurrence of thrombosis 60 minutes after anastomosis.Results From November 2015 to April 2018, 247 anastomoses were performed on 229 arteries and 18 veins. One hundred twenty-five anastomoses were irrigated with physiological salt solution, 122 with pure unfractionated heparin. A 60-minute thrombosis was found on 31 anastomoses (25%) irrigated with physiological salt solution compared with 16 anastomoses (13%) irrigated with heparin, that is, a decrease in the thrombosis rate of 2.6 (p = 0.01).Conclusion The use of pure unfractionated heparin in intraoperative lumen irrigation during microsurgical end-to-end anastomoses reduces the rate of vascular 60-minute thrombosis compared with physiological salt solution irrigation. It is an effective intraoperative procedure for the prevention of microsurgical thrombosis.
Keywords: heparin; thrombosis; end-to-end anastomosis; microsurgery; free flap